2004
DOI: 10.1255/jnirs.407
|View full text |Cite
|
Sign up to set email alerts
|

Development of Wood Property Calibrations Using near Infrared Spectra Having Different Spectral Resolutions

Abstract: A range of important wood properties can be predicted using calibrations obtained using SilviScan data and diffuse reflectance near infrared (NIR) spectra collected from wooden strips cut from increment cores. The ease of NIR measurements and the rapid provision of SilviScan data provides the opportunity to establish extremely large data sets, causing calibration problems. An option is to reduce the number of data points representing an individual NIR spectrum. NIR spectra were collected in 10 mm increments fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
14
2
2
Order By: Relevance
“…All spectrums were averaged at 10‐nm intervals prior to data analysis. It has been shown that a 10‐nm average has no detrimental influence on model precision and performance (Schimleck and others 2004).…”
Section: Methodsmentioning
confidence: 99%
“…All spectrums were averaged at 10‐nm intervals prior to data analysis. It has been shown that a 10‐nm average has no detrimental influence on model precision and performance (Schimleck and others 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Forty scans were acquired at 1 nm intervals using reflectance spectroscopy and then averaged. The 1 nm intervals were next averaged into 10 nm intervals with no loss in spectral resolution (Schimleck et al 2004). The spot size of the scanning area was 5 mm.…”
Section: Nir Spectroscopymentioning
confidence: 99%
“…A técnica NIRS tem provado ser ferramenta útil nos programas de melhoramento para seleção de espécies envolvendo grande número de árvores (SCHIMLECK et al, 2004), e os pesquisadores pioneiros dessa técnica em madeira foram Birkett e Gambino (1998), Easty et al (1990) e Wright et al (1990). Muitos trabalhos relacionam a utilização de NIRS para análises de propriedades químicas da madeira como lignina e extrativos (BRINKMANN et al, 2002;GIERLINGER et al, 2002;BOERIU et al, 2004;ALVES et al, 2006) e de propriedades físicas como a densidade básica (HOFFMEYER;PEDERSEN, 1995;SCHIMLECK et al, 1999;SCHIMLECK et al, 2004;HEIN et al, 2009).…”
Section: Introductionunclassified
“…Muitos trabalhos relacionam a utilização de NIRS para análises de propriedades químicas da madeira como lignina e extrativos (BRINKMANN et al, 2002;GIERLINGER et al, 2002;BOERIU et al, 2004;ALVES et al, 2006) e de propriedades físicas como a densidade básica (HOFFMEYER;PEDERSEN, 1995;SCHIMLECK et al, 1999;SCHIMLECK et al, 2004;HEIN et al, 2009).…”
Section: Introductionunclassified